The relationship of race discipline with overall performance in sprint and standard distance triathlon age-group world championships - Horne, M. J. (International Journal of Sports Science & Coaching, 2017)
The study analysed data of 25- to 29-year-old athletes from the 2015 International Triathlon Union Age-group World Championship. Four separate draft-illegal races were analysed (male standard, male sprint, female standard and female sprint). The correlation of individual race disciplines with overall finish time, and the variance accounted for by each discipline was considered. Running had the strongest relationship with finishing time in standard racing. Cycling had the strongest relationship in sprint racing. There were no gender differences in correlations or in the greatest predictors of performance. It was concluded that the importance of running in predicting triathlon performance seen in previous research on standard distance racing is not due to the legality of drafting in the cycle discipline. ABSTRACT FROM AUTHOR